Industrial archaeoacoustics, methods and applications in heritage safeguarding. The case of the MNACTEC Territorial System project “The Sounds of Industry” - Emilio Marx; Ginebra Raventós de Volart; Edgardo Gómez Ortiz (Treballs d'Arqueologia)
Archaeoacoustics, an interdisciplinary field that combines archaeology, acoustics and computer modeling, traditionally researches the sonic dimensions of ancient cultures, revealing insights beyond conventional methods. This article, however, extends these techniques to the preservation of industrial heritage based on a critical heritage perspective. By focusing on the MNACTEC museum network’s project “The Sounds of Industry”, it illustrates how capturing, analyzing and recreating the sounds of the industrial past can enhance heritage conservation. By providing immersive auditory experiences, archaeoacoustics presents a unique method for connecting contemporary audiences with the industrial past. This study underscores the potential of sound-based heritage projects to deepen public understanding and appreciation of historical narratives.